THE IMPACT OF LEARNING ENVIRONMENT ON STUDENTS’ LEARNING MOTIVATION IN ISLAMIC RELIGIOUS EDUCATION AT VOCATIONAL HIGH SCHOOL - Abdul Ghofur; Eka Abdul Hamid; Moch. Hilman Taabudilah (STAI Sebelas April Sumedang, 2026)
Learning motivation is an important factor that determines the success of students in the learning process. One of the external factors that is assumed to influence learning motivation is the learning environment, which includes the family environment, school environment, and community environment. A conducive learning environment is believed to create a comfortable learning atmosphere that can increase students’ engagement in the learning process. This study aims to analyze the condition of the learning environment, the level of students’ learning motivation, and the influence of the learning environment on students’ learning motivation in Islamic Religious Education subjects at SMK Ardli Sela Conggeang. This research used a quantitative approach with a descriptive correlational method. The population of this study consisted of all tenth-grade students totaling 32 students, and the entire population was used as the sample through the saturated sampling technique. Data were collected through questionnaires, observations, and documentation, while data analysis was conducted using descriptive statistical analysis and correlation analysis with the help of the SPSS program. The results showed that the students’ learning environment was categorized as very good with a percentage of 88%, while students’ learning motivation was categorized as very good with a percentage of 90%. The coefficient of determination analysis showed that the learning environment had an influence on students’ learning motivation of 10.89%, which is categorized as very weak. These findings indicate that students’ learning motivation is not only influenced by the learning environment but also by other factors such as learning interest, learning strategies, and family support. This study implies that efforts to improve students’ learning motivation need to be carried out comprehensively through the creation of a conducive learning environment and the implementation of innovative learning strategies.